Performance of Hybrid Rice Husk and Kapok Fiber as Alternative Liner Materials in Landfill - Muhamad Bashar, N.A.; Abdullah, N.H.H.; Abdul Aziz, N.H.; Fahmi, N.I.H.; Saiful Bahri, I.S.; Hamzah, N.; Abdul Wahab, K.; Razali, W.N. (Journal of Advanced Manufacturing Technology (JAMT), 2018)
Generation of waste from agricultural activities like rice husk (RH) and kapok fiber (KF) is on the rise annually. Some of the arising issues are landfill limitation and air pollution because of burning activities. This paper presented a potential application of agricultural waste as an alternative material in landfill. A series of standard tests were conducted such as hydraulic conductivity test (falling head method), batch adsorption test (COD, TSS and heavy metals testing). These tests were conducted in the ratio of 1:1 and 1:2 of hybrid RH:KF. The results yielded that the hydraulic conductivity of the hybrid RH:KF in the ratio of 1:1 was lesser than 10-9 m/s, satisfying the requirement of landfill liner. The hybrid arrangement (RH:KF) for 1:1 ratio as adsorption media was able to reduce at least 45% of the bulk parameter (COD) whereas for 1:2, ratio, about 43.5% of heavy metal (Zn) was reduced in leachate. The proposed hybrid arrangement (RH:KF) is a green material for the landfill (bulk parameters and heavy metal adsorption capacity) that improves landfill workability, minimizing manpower on site and cost.